Bulk phase Behavior and displacement performance of CO2 foam induced by a combined foaming formulation - Xu, X.; Saeedi, Ali; Liu, K. (Elsevier, 2016)
To overcome the viscous fingering and gravity segregation of CO2 flooding, a combined foaming formula (AOS/AVS/N70K-T) was proposed and compared with two well-known foaming formulas (i.e. AOS alone and AOS/HPAM). The assessment results indicated: 1) the proposed AOS/AVS/N70K-T noticeably balanced the foamability and foam stability in a reasonable manner (the foamability is larger than 500 ml and the foam stability is greater than 2000 s); 2) its apparent viscosity in high permeability rocks could increase by 36.3% compared to that in low permeability rocks; 3) the foam generated by direct injection mode endowed better blockage than the co-injection of the gas or solution, which could be validated by the investigations of the resistance factor (RF) and residual resistance factor (RRF); 4) the mobility reduction factor (MRF) of the AOS/AVS/N70K-T foam achieved the optimal value at an intermediate total gas/solution flow rate (with fixed gas/liquid ratio of 3:1), while its MRF dropped as gas flow rate rose. 5) The proposed formula displayed pronounced advantages over the other two foaming formulations in all of the respects mentioned above. Through the extensive studies, it is believed that the new formula combination might possess huge potential applications in CO2 Enhanced Oil Recovery (EOR).